Low level of serum Hemoglobulin concentration associated with neonatal birth weight (Bangladesh Journal of Medical Science, 2020)
Background: Lower level of maternal serum hemoglobin (Hb) concentration may cause adverse pregnancy outcome (LBW, Preterm delivery) have been inconsistent. Many studies have been shown the impact of Hb concentration and protein status on pregnancy outcome in GA